PEMBERITAAN KEMURNIAN FIRMAN TUHAN DI TENGAH-TENGAH TANTANGAN KAPITALISME - Sibuea, Andreas Filemon; Sitanggang, Pintor Marihot (Sekolah Tinggi Teologi Satyabhakti, East Java, 2025)
Capitalism, with its strong influence on culture, economy, and social values, often distracts from the core of Christianity. Therefore, this paper aims to identify the challenges the church faces in maintaining the authority of the Bible amidst the influence of capitalism, as well as offer solutions and steps that can be taken to maintain the purity of the proclamation of God's Word. Capitalism often encourages an excessive focus on materialism, wealth and personal success, which can erode Christian values such as love, humility and self-sacrifice. Churches may be tempted to change the gospel message to better suit the values of capitalism, which can ultimately undermine the purity of God's Word. In addition, there is concern that in a world driven by a market economy, the priorities of the church may shift from ministry and spiritual mission to being more oriented towards economic growth or financial over-management. The question raised is: how can the church remain faithful to the authority of the Bible and proclaim the purity of God's Word in the face of capitalist cultural pressures? To achieve the purpose of writing this article, it begins with a biblical foundation study followed by a theological discussion from a Christian perspective which then presents the church's teaching in facing the challenges of capitalism.